A mechanistic study on the biosynthetic regulation of bioactive metabolite Antroquinonol from edible and medicinal mushroom Antrodia camphorata. (August 2016) - Hu, Yong-Dan; Zhang, Bo-Bo; Xu, Gan-Rong; Liao, Xiang-Ru; Cheung, Peter C.K.
Highlights: Antroquinonol is a bioactive metabolite from the mushroom Antrodia camphorata . Biosynthesis of antroquinonol was stimulated by addition of precursors and effectors. Coenzyme Q0 can regulate the expression of key proteins in its biosynthetic pathway. Camphorwood leach liquor acts as donor of quinone nucleus for antroquinonol synthesis. Soybean oil increases cell permeability and extraction efficiency for antroquinonol. Abstract: Antroquinonol, an important bioactive metabolite from the edible mushroom Antrodia camphorata, was difficult to be synthesised by conventional submerged fermentation. The present study revealed the mechanisms related to the stimulatory effect of coenzyme Q0, camphorwood leach liquor and soybean oil on the biosynthesis of antroquinonol. Addition of coenzyme Q0 could up-regulate the expression of S-adenosylmethionine synthetase, affording methyl group for the biosynthesis of antroquinonol. Heat shock proteins and tricarboxylic acid cycle related proteins were found to participate in the biosynthetic pathway. Camphorwood leach liquor could provide the precursor of antroquinonol by acting as donor of quinone nucleus. Soybean oil could increase the permeability of mycelial cell membrane and the extraction efficiency for the intracellular hydrophobic antroquinonol. This study advances our understanding on how stimulatory agents can be used to regulate the biosynthesis of valuable metabolites produced from mushroom mycelia and facilitate the development of submerged fermentation for potential industrial application.